Building Village through MBKM Learning Model with KUKIS: Students Perceptions on the Learning Outcomes and MBKM Goals - Samad, Ita Sarmita; Jabri, Umiyati; Akbar, Imam (Sublim: Jurnal Pendidikan, 2023)
This research aims to analyse the impact of the MBKM-based KUKIS learning model, the village building scheme, which has been applied to students of English Education study program. The KUKIS learning model is adapted from the Project-Based Learning model. Descriptive research method with a quantitative approach is used in this research. Questionnaires and interviews are used as instruments to collect data from the selected research sample using purposive sampling technique. The results of data analysis show that the application of KUKIS is able to contribute positively to students' ability to fulfil learning outcomes which include attitudes, general skills, special skills, and mastery of knowledge. Likewise for the aspect of MBKM objectives, students assessed that the application of the KUKIS learning model is able to contribute positively to the achievement of MBKM goals, both soft skills and hard skills of students.